Impact of the Tips From Former Smokers Anti-Smoking Media Campaign on Youth Smoking Behaviors and Anti-Tobacco Attitudes. Issue 12 (24th June 2022) - Slocum, Elizabeth; Xie, Yanmei; Colston, David C; Emery, Sherry; Patrick, Megan E; Thrasher, James F; Elliott, Michael R; Fleischer, Nancy L
Abstract: Introduction: Anti-tobacco media campaigns can prevent youth smoking, but there is little research on how adult-targeted campaigns affect youth. We investigated the association between the Tips From Former Smokers (Tips) campaign and youth smoking behaviors and anti-tobacco attitudes, and variation by sex, race and/or ethnicity, or socioeconomic status. Aims and Methods: We used data from the monitoring of the future study, a nationally representative survey on 8th, 10th, and 12th graders, from 2013–2015. Quartiles of Tips gross rating points (GRPs) were used to estimate exposure. Youth smoking behavior outcomes included smoking prevalence, initiation, and susceptibility. The anti-tobacco attitude outcomes included the extent that anti-tobacco ads made participants (1) less favorable towards smoking or (2) less likely to smoke cigarettes. Modified Poisson regression models estimated average marginal effects; separate additive interactions between Tips GRP exposure and sex, race and/or ethnicity, parents' highest education, and college plans (12th graders only) were used to test for effect modification. Results: Tips GRPs were not associated with smoking behaviors within any grade. However, 12th graders in the highest quartile of Tips had a 7.0 percentage point higher probability (95% CI = 0.023–0.116) of responding that anti-tobacco ads made them less likely to smoke. Tips GRPs were associated with a lower probability of past 30-day smoking prevalence among 10th grade females, but not males (joint P -value = .002). No additional statistically significant interactions were found for any other outcomes for any grade. Conclusions: This study revealed the potential for adult-targeted campaigns to increase youth's anti-smoking attitudes, but campaign exposure was not associated with smoking behaviors. Implications: Few studies have examined the potential for anti-smoking media campaigns to influence audiences outside their targeted audience. In this study, we show the potential for adult-targeted campaigns to impact youth and suggest that Tips exposure may promote anti-smoking attitudes among youth.